Sensory activities as part of a cultural tourism route for the Festival de Artes Vivas de la Ciudad de Loja (Living Arts Festival of the City of Loja) - Suárez-Jaramillo , Gladys Alexandra; Ortega-Barba, Grace Melina; Briceño Luzuriaga, Yesenia Alexandra (Journal of business and entrepreneurial studie, 2023)
This work was carried out with the objective of elaborating a proposal for a sensory tourism route of art and culture for the FIAVL, based on a selection of attractions under specific criteria of: availability, accessibility, safety, in addition to their relationship with the senses and how these senses are perceived in an attraction by the tourist; this is how the attractions that will act as the basis of this route were chosen. Based on these, together with the bibliographic review and the visitor's opinion or demand, the sensory tourism activities were defined; the second important factor for the route. With these two factors, we proceeded to design the "Sensory Route: Feel Loja", a cultural tourism route that involves the five senses: sight, touch, smell, taste and hearing. The attractions are related to activities that stimulate these senses, and at the same time allow the visitor to learn more about the history and culture of the city of Loja. The methodology proposed for this research work was of the exploratory type, since no route of this type has been carried out in the city, and it also has a quantitative and qualitative approach. Bibliographic consultations were carried out, survey of tourist attractions: data sheet adapted to the methodology of the MINTUR and technical data sheets of the INPC, data collection through survey technique and Focus Group, among others.